Social Influence on Motivation and Job Insecurity among Thai Gig Economy Riders - Thepprasarn, Teerathep; Suntrayuth, Sid (Asia Social Issues, 2025)
This research study provides insight into the gig economy’s operational form in Thailand, focusing on digital platform-driven employment, specifically for motorbike riders. It extends current research by exploring the socio-economic impacts, job uncertainty, and the interaction between extrinsic and intrinsic incentives. The study employs a quantitative methodology using a cross-sectional survey and structural equation modeling to assess gig workers’ perceptions of job insecurity. The model includes social influence, motivation, and demographic factors. The results reveal that perceived social pressure influences extrinsic and intrinsic motivation and job insecurity. Intrinsic motivation is identified as a protective factor against job insecurity, emphasizing the need to align gig work with workers’ preferences, needs, and values, with a focus on mental health. In contrast, extrinsic motivation increases job insecurity and is positively linked with extrinsic motivation, highlighting the mutual relationship between monetary rewards and insecurity. This research fills a gap in understanding Thailand’s gig economy and supports developing policies and platform designs that capture motivational gains while addressing the socio-economic challenges faced by gig workers. It provides guidance on promoting an optimistic gig economy, including social protection measures, fair wages, and employment legislation to protect gig workers.